2018
DOI: 10.1016/j.dib.2018.10.115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical data and risk factors for diabetic nephropathy in Brazilian central population

Abstract: This article describes data set of the profile of patients diagnosed with Diabetic Nephropathy (DN) undergoing hemodialysis and followed-up by Hemodialysis Service in medical centers in Goiânia, Go, Brazil. These data describe specifically the demographic, clinical, and lifestyle variables of 101 patients. In addition, these data provide detailed clinical associations about the profile of patients diagnosed with DN and which are made publicly available to enable critical or extended analyzes. For further inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Diabetic nephropathy is a chronic kidney disease caused by diabetes-related complications, including proteinuria and glomerulosclerosis. It is known to affect ~30% of patients with type 1 diabetes and ~10% of patients with type 2 diabetes ( 1 ). Numerous studies have reported the use of metformin in the treatment of various medical conditions in humans such as diabetes ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetic nephropathy is a chronic kidney disease caused by diabetes-related complications, including proteinuria and glomerulosclerosis. It is known to affect ~30% of patients with type 1 diabetes and ~10% of patients with type 2 diabetes ( 1 ). Numerous studies have reported the use of metformin in the treatment of various medical conditions in humans such as diabetes ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is the leading cause of end-stage renal disease (ESRD) worldwide ( 1 ). The development of DN is associated with hypertension, elevated urinary albumin levels, glomerulosclerosis and a decline in the glomerular filtration rate, ultimately resulting in ESRD ( 2 ).…”
Section: Introductionmentioning
confidence: 99%